تخمين اعمار الخزانات تحت تاثير المنتوجات النفطية المختلفة - حمد, د. جمال محمد (Journal of Petroleum Research and Studies, 2013)
In this study five oil solutions were used to measure the corrosion of the metal tank which was used. This tank is used to hold the oil productions and is made of an alloy called low carbon steel. These solutions are Benzene, water associated with benzene, Gas oil, water associated with the gas oil, and water associated with the crude oil. A three sample were choosing of each solution and the average was taken in order to get a precise result. Also the study clear field that the danger is located in lowest part of the tank because of the existence of the water however, the specific gravity of water is greater than the specific gravity of the benzene and gas oil. For this reason we have to super water associated even though the loss of a product to increase the duty time and ageing of the used tank.